Origins and carriers of Sb, As, Cd, Cl, Cr, Co, Pb, Hg, and Ni in mixed solid waste – A literature-based evaluation. (15th February 2020) - Viczek, S.A.; Aldrian, A.; Pomberger, R.; Sarc, R.
Highlights: Carriers of 9 elements in waste are identified based on literature. Concentrations and expected ranges of elements in carriers are listed. Metals, inerts, composites and plastics are important contaminant carriers. Some important carriers (metals etc.) are often not reflected by chemical analyses. Removing contaminant carriers can improve waste fuel quality and decrease emissions. Abstract: Antimony, arsenic, cadmium, chlorine, chromium, cobalt, lead, mercury, nickel and their compounds are commonly used in the industrial production of various goods. At the end of the product life cycle, these elements enter the waste system as constituents of the products. Mixed municipal and commercial wastes are landfilled, biologically treated, incinerated, and/or processed in mechanical treatment plants to yield solid recovered fuel (SRF). In all these cases, inorganic contaminants that are present in the input waste material play a significant role. In mechanical waste treatment, materials containing high concentrations of these elements (contaminant carriers) can be selectively removed (e.g. by infrared sorters) to improve the output quality, but prior knowledge about the contaminant carriers is required. This paper reviews several waste-related publications in order to identify carriers of Sb, As, Cd, Cl, Cr, Co, Pb, Hg, and Ni in mixed municipal and commercial waste. Identified contaminant carriers are listed alongside ranges for expected concentrations. Furthermore, the data are combined with information on industrial applications and contaminant concentrations in products in order to discuss the reasons for the presence of the respective elements in the carriers. Generally, besides inerts or metals, identified contaminant carriers often include plastics, composite materials, leather products, textiles, rubber, electronic waste, and batteries. Moreover, it is evaluated how individual contaminant carriers are reflected by chemical waste analyses. While the findings of the paper can be applied to different waste treatment options, the discussion focuses on SRF, which is the main output of mechanical treatment plants.